Sur un nouveau modèle de bassin pour l'élevage de jeunes salmonidés - Billard, Roland; Petit, Jean (HAL CCSD, 1973)
A new circular-shaped tank for rearing young Salmo salar, designed by Dr. D. H. Marr and now in use at the Almondbank salmon farm in Scotland, is described and compared with other types in current use. Basically the water is fed into the centre of the basin thus allowing for better spatial distribution of the allevins. The inlet pipe reaches down up to 2-3 cm of the bottom. A peripherally located outlet pipe collects the faeces and residual food pellets. Another pipe for automated food pellets (smaller diam) connects with the inlet water pipe at the point where it bends at right angles down to the bottom. In this manner O sub(2), water and food are distributed homogeneously. There are 2 sizes of tank: (1) 35 cm in height for young alevins, 2-3 months old; (2) 60 cm in height for young parrs, 4-10 months old. The results obtained from initial experiments using these rearing tanks are very encouraging with a notable reduction in fish mortality rate.